Fostering students’ mathematical reasoning through a cooperative learning model - Angel Mukuka; Jogymol Kalariparampil Alex (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study sought to ascertain whether the student teams-achievement division (STAD) model of cooperative learning is effective in fostering students’ mathematical reasoning. Using the cluster random sampling technique, 301 eleventh-grade students between the ages of 14 and 20 were chosen from six public secondary schools within one district in Zambia. Students were given tasks on quadratic equations and functions both before and after the intervention. A robust analysis of the covariance test revealed that students’ mathematical reasoning abilities were significantly higher for the group that received instruction using the STAD approach than for the group that was taught using conventional methods of instruction at each of the five design points where regression slopes were comparable. A Chi-square test of independence further revealed that the STAD learning approach was associated with a greater proportion of students who demonstrated an appropriate degree of mathematical reasoning ability for each of the three indicators (conjecturing, justifying, and mathematizing). These results demonstrate that enhancing students’ mathematical reasoning abilities through the integration of classroom activities that engage students intellectually, physically, and socially is beneficial.